Ethnomedicine to Modern Medicine: Genesis through Ages - Patil*, D. A. (Journal of Experimental Sciences, 2011)
<span style="font-size: 8pt; color: black; font-family: ";Tahoma";,";sans-serif";; letter-spacing: -0.05pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Ethnomedicine or natural products have encouraged several developments in drug discovery. There are many historical annals in which ethnomedicine helped to divulge navel aspects of drug isolation. Studies in ethnomedicine are the pioneer natural attempts to combat human afflictions. Their history itself witnesses how they paved their way to classic medicine. The present paper brought these all phases of medicine beginning with the ancient human knowledge to modern times. The necessity and challenges faced during drug discovery especially from ethnomedicinal plants is briefly discussed. Today, we need to have new innovative approaches for drug discovery. These are highlighted with particular emphasis on ethnomedicine.